Molecular Genetic Analysis of sup45 Paromomycin Hypersensitive Mutants In Saccharomyces cerevisiae - Rukman Hertadi; Hadi Sutedjo; Akhmaloka Akhmaloka (Institut Teknologi Bandung, 2001)
Translation termination in Saccharomyces cerevisiae is mediated by eRF-1 and eRF-3 protein encoded by SUP45 and SUP35 gene respectively. To probe more detail concerning the mechanism of translation termination in this organisms, the structure-function of the eRF-1 protein was studied by analyzing of sup45 mutants. In this study, we used three paramomycin hyper sensitive mutants, namely sup45-23, sup45-24 and sup45-38. Phenotypic characterization and quantitation of allosuppresor level showed that the mutants were allele specific mutants. Cloning and sequencing of the sup45 genes from these mutants showed that the sup45-23 exhibited Met48ATG â Ile48Ala and Gly431GGT â Gly431GGA mutation. While sup45-24 and sup45-38 exhibited single silent mutation, Gly431GGT â Gly431GGA . The structure-function analysis of sup45 gene of these mutant suggested that phenotypic mutants were not only due to the alteration of amino acid of eRF-1 protein in the cells.